Post-Market in vitro bioequivalence study of innovator and generic Gefitinib tablets: evaluation of JKN medicine quality - Nurhayati, Fitri; Anggriani, Yusi; Syahruddin, Elisna; Andalucia, Rizka; Ath-Thobari, Jarir; Mulatsari, Esti (Faculty of Pharmacy, Universitas Pancasila, 2024)
Gefitinib is one of Tyrosine Kinase Inhibitors (TKIs), as first line therapy for Non-Small Cell Lung Cancer (NSCLC) with positive EGFR mutation. Gefitinib started to be accommodated in Jaminan Kesehatan Nasional (JKN) insurance in 2015 with the innovator gefitinib and was replaced by a generic product in middle of 2021. This research was conducted to see whether the quality of generic gefitinib equivalent to the innovator through post-market in vitro bioequivalence test. Assay method refers to previous research by Sandhya et al 2013 wih High Performance Liquid Chromatography (HPLC), while the dissolution test method is in accordance with the Food and Drug Association (FDA) 2010. We collected innovator from the official distributor and 3 batches (all batches that have been used in JKN program) of generic product from hospitals where lung cancer therapy services were provided. We evaluated the dissolution profile with similarity and unsimilarity factors and assess based on standard specification of dissolution profile that informed in innovator’s BPOM-approved brochure (avarage of 6 samples > 85% and no individual result < 75% at 45 minutes). The assay results met the requirements of ± 5% of what is stated on the label. Although dissolution profile of generic and innovator were not equal through difference and similarity factors calculation, but one batch of generics met dissolution profile standard of innovator. So, both generic and innovator drug met the standards of assay and dissolution, even though the dissolution profile were not equivalent.